2012
DOI: 10.1088/0004-637x/749/2/148
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Polarization Reverberation in NGC 4151

Abstract: Observations of the optical polarization of NGC 4151 in 1997NGC 4151 in -2003 show variations of an order of magnitude in the polarized flux while the polarization position angle remains constant. The amplitude of variability of the polarized flux is comparable to the amplitude of variability of the total U -band flux, except that the polarized flux follows the total flux with a lag of 8 ± 3 days. The time lag and the constancy of the position angle strongly favor a scattering origin for the variable polariza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 32 publications
(45 reference statements)
2
40
1
Order By: Relevance
“…However, while the explanation of the high P detected in particular type-1 AGN might be an addition of the last three mechanisms proposed above, it is important to recognize that we have restricted the analysis in this paper to axially-symmetric situations while real AGNs are certainly messier and simple asymmetry could be the explanation. The significant long-term variability of the degree of polarization in Mrk 231 while the angle stays constant is qualitatively similar to what Gaskell et al (2012) discussed for NGC 4151. As with NGC 4151, polarimetric reverberation mapping could give important information about the location of the main scattering region responsible for the relatively high polarization in Mrk 231.…”
Section: Polarization At Type-1 and Type-2 Viewing Anglessupporting
confidence: 80%
See 1 more Smart Citation
“…However, while the explanation of the high P detected in particular type-1 AGN might be an addition of the last three mechanisms proposed above, it is important to recognize that we have restricted the analysis in this paper to axially-symmetric situations while real AGNs are certainly messier and simple asymmetry could be the explanation. The significant long-term variability of the degree of polarization in Mrk 231 while the angle stays constant is qualitatively similar to what Gaskell et al (2012) discussed for NGC 4151. As with NGC 4151, polarimetric reverberation mapping could give important information about the location of the main scattering region responsible for the relatively high polarization in Mrk 231.…”
Section: Polarization At Type-1 and Type-2 Viewing Anglessupporting
confidence: 80%
“…The spectral flux and polarization were computed and discussed in the context of observed spectropolarimetric data and of the modeling work done by other groups. In our subsequent work, we have explored the polarization induced by different dust compositions in the torus or the polar outflow (Goosmann et al 2007a,b), compared two competitive scenarios to explain the emergence of the broad Fe Kα line in the Seyfert 1 galaxy MCG-6-30-15 (Marin et al 2012b), investigated time-dependent polarization due to reverberation Gaskell et al 2012), and investigated the effect of an inflow velocity of the scattering medium on the shape of AGN emission lines .…”
Section: Applying the Radiative Transfer Code Stokesmentioning
confidence: 99%
“…This is where the polarization reverberation mapping technique is the most valuable. Gaskell et al (2012) demonstrated how the polarization variability in NGC 4151 can be used to probe the size and structure of scattering regions. Between 1997 and 2003, the type-1 radio-quiet AGN NGC 4151 has shown variations of an order of magnitude in its optical polarized flux while its polarization position angle remained constant.…”
Section: Polarization Reverberation Mappingmentioning
confidence: 99%
“…As has already been pointed out in Section 4.1, the two observations made by ESO3.6-m/EFOSC2 and Keck/LRIS on 1st May, 2002, and4th May, 2003, respectively (separated by one year, i.e., by 0.8 years in the quasar rest frame), show coordinated variability between the total and polarized fluxes. With the assumption that the polarization in 3C 323.1 is due to scattering of the disc continuum, the time lag between the total flux variation (disc continuum flux) and the polarized flux variation (scattered flux) corresponds to the light travel time across the accretion disc and the scattering region (e.g., Gaskell et al 2012). Therefore, the observed coordinated variability of the total and polarized fluxes directly constrains the radial distance of the scattering region as…”
Section: Radial Extent Of the Scattering Region Inferred From The Polmentioning
confidence: 99%
“…In addition, some authors have claimed that the intrinsic quasar accretion disc continua must be completely depolarized because of the strong Faraday depolarization with magnetic fields in the disc atmosphere (Agol & Blaes 1996;Silant'ev et al 2009, and references therein). Instead, the observed optical polarization properties in type 1 quasars can be understood by assuming a geometrically and optically thin equatorial electron-scattering region located inside the dust torus; photons produced inside this electron-scattering region can be scattered into our line of sight, resulting in a net linear polarization "parallel" to the disc rotation axis (e.g., Stockman et al 1979;Antonucci 1988;Smith et al 2004Smith et al , 2005Goosmann & Gaskell 2007;Kishimoto et al 2008a;Batcheldor et al 2011;Gaskell et al 2012;Marin & Goosmann 2013;Hutsemékers et al 2015;Silant'ev et al 2016). It is currently believed that all AGNs/quasars have both equatorial and polar scattering regions, and that differences in the observed polarization properties between type 1 and type 2 objects are due to the orientation effect (e.g., Smith et al 2004).…”
Section: Introductionmentioning
confidence: 99%